PENGARUH TERMINAL FEEDBACK TERHADAP KETERAMPILAN LAY UP BOLA BASKET PADA MAHASISWA PENDIDIKAN OLAHRAGA 2022 STKIP PGRI BANGKALAN - Wahyuni, Ani; Hidayatullah, Fajar; Yuli Handayani, Heni (Fakultas Ilmu Keolahragaan Unimed, 2024)
Students in doing lay up movement exercises need external encouragement such as feedback. Feedback is an explanation that comes out of the results of the movement while terminal feedback is an explanation that is carried out after the activity occurs. The experiment will take place, there will be reinforcement given by the researcher for each tester doing the lay up movement. Every time the lay up movement activity is completed, the researcher will carry out terminal feedback. The results of the Wilcoxon test are known to be Sig. with a value of 0.001 <0.05, it can be concluded that there is a difference between the pre-test and post-test of lay up skills, so the conclusion is